JUMAT MAKAN SEHAT: MEMBENTUK KEBIASAAN GIZI BAIK SEJAK USIA DINI DI TK AR-RAHMAN - Yusria; Budiyani; Elawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The establishment of healthy eating habits from an early age is a strategic step in creating a strong and healthy generation. The Healthy Eating Friday (JUMASE) program at Ar Rahman Kindergarten aims to introduce and familiarize children with nutritious foods through routine activities carried out every Friday. This article uses a descriptive qualitative approach with data collected through observation, interviews with teachers and parents, and documentation of activities. The research findings indicate that the JUMASE program plays a role in enhancing children's awareness and healthy eating habits, supported by the active involvement of teachers and parents. This program can serve as a reference model for promoting balanced nutrition in other early childhood education institutions.